2015
DOI: 10.1155/2015/815132
|View full text |Cite
|
Sign up to set email alerts
|

A New Fast Algorithm for Constrained Four-Directional Total Variation Image Denoising Problem

Abstract: A new four-directional total variation (4-TV) model, applicable to isotropic and anisotropic TV functions, is proposed for image denoising. A dual based fast gradient projection algorithm for the constrained 4-TV image denoising problem is also reported which combines the well-known gradient projection and the fast gradient projection methods. Experimental results show that this model provides in most cases a better signal to noise ratio when compared to previous models like the reference TV, the total general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Further, based on TV4, Liao et al improved the boundary conditions and provided a complete mathematical proof for both anisotropic and isotropic cases [32]:…”
Section: Four-directional Total Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, based on TV4, Liao et al improved the boundary conditions and provided a complete mathematical proof for both anisotropic and isotropic cases [32]:…”
Section: Four-directional Total Variationmentioning
confidence: 99%
“…In contrast, the TV method can only minimize horizontal and vertical gradients, reducing image noise in the horizontal and vertical directions, whereas the four-direction gradient regularization approach can reduce noise in the 45 • and 135 • directions, thereby improving the quality of image reconstruction [31,32]. Based on the four-direction TV (TV4) proposed by Sakurai et al [31], Wu et al presented a four-directional fractional-order TV (FTV4) [33], which applies the fractional-order difference operator to alleviate the staircase artifacts in TV4 and improve its denoising ability.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of single direction constraint over a limited angle tomographic image taken from both x and y directions also showed that the directional information plays an important role in feature preservation in the image taken from a limited view angle ( Zhang et al, 2021 ). There have been alternative modified gradient based total variation algorithms ( Zhang et al, 2021 ; Sakurai et al, 2011 ; Fan Liao & Shu, 2015 ; Huang et al, 2016 ; Huang et al, 2018 ; Hu & Jacob, 2012 ; Zhou & Fan, 2021 ). Sakurai et al proposed a faster four directional TV algorithm that brings two additional partial terms to the horizontal and vertical directional terms in classical TV ( Sakurai et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Four-directional total variation (TV4) [26] can make full use of the neighbor gradient information of each pixel. A new four-directional total variation model proposed by Liao et al [27] takes gradient information in the diagonal and back-diagonal directions into account. They solved the optimization problem with gradient projection (GP) and also given a complete mathematical proof for the first time.…”
Section: Introductionmentioning
confidence: 99%